(untitled) (Movimenta (ISSN 1984-4298), 2025)
Objective: To assess the quality of life (QoL) of elderly people undergoing a cardiovascular exercise program at a health center. Basic procedures: A quasi-experimental study was conducted with 21 elderly individuals undergoing treatment in the FISIOCAP program (cardiovascular physiotherapy in primary care), who consented to participate in this study and responded to the sociodemographic questionnaire and the Short Form Health Survey 36 (SF-36) questionnaire to assess QoL before and after three months of intervention, with cardiovascular physical therapy sessions twice a week in the morning with group exercises, divided into warm-up phases with a 10-minute walk, conditioning with exercises such as climbing up and down stairs, performing an obstacle course, sitting down and getting up from a chair, a 10-minute cool-down phase with stretching and breathing exercises, and 10 minutes of health education guidance. Results: The sample had a higher prevalence of male elderly individuals (66.7%), with a mean age of 70.52 years, mean height of 1.60 ± 0.08, and mean weight of 73.63 ± 11.87. Statistical analysis showed a significant improvement in the functional capacity (p<0.018) and mental health (p<0.042) domains on the SF-36. Mental health and functional capacity improved, indicating positive effects of regular physical activity on the overall perception of well-being among older adults. Conclusion: The cardiovascular physical therapy program proved effective in improving the QoL of the elderly, especially in domains critical to autonomy and well-being. The findings suggest that cardiovascular physical therapy programs are viable and beneficial strategies for the overall health of the elderly.